Regression Analysis of Financial Literacy Moderation to Increase Interest in Investing in the Capital Market in Atmi Surakarta Students - Kartikasari, Dewi; Kusumawati, Evi Dewi; Putra, Alfa Santoso Budiwidjojo (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
This research aims to prove and analyze empirically how minimum capital and investment understanding affect investment interest and the interaction that occurs between minimum capital and financial literacy affect investment interest and the interaction of investment understanding and financial literacy affect investment interest. The object of this research is students of the Industrial Mechanical Engineering Academy. The population of this study was 168 students majoring in mechanical engineering. The sample selection technique used was simple random sampling so as to obtain a sample of 84 students. This research uses a quantitative approach. The analysis technique in this study uses moderation regression. The research data has passed the validity test, reliability test, classical assumption test, adjusted R2 test, multiple linear regression test, t test, F test. The results showed that minimum capital and investment understanding affect investment interest. Financial literacy can moderate the effect of minimum capital on investment interest. Financial literacy can also moderate the effect of investment understanding on investment interest.